Analysis of Healthy Alert Personal Selling Strategy at PT Mitra Antar Putra in South Jakarta - Hardiansyah, Novan Fariz; Pasaribu, Veta Lidya Delimah (Asian Journal of Applied Business and Management, 2024)
PT Mitra Antar Putra has a sales division which applies personal selling to market PT. Mitra Antar Putra currently has 2 departments, namely Inbound Acquisition and Outbound Acquisition where each department has a unit/team. Personal selling activities by the sales department. The focus of this research is how to explain current strategies, conditions, and alternative personal selling strategies. This comprehensive method uses qualitative methods, and the techniques used are interviews, documentation, observation, analytical methods used for data collection, data reduction and data display. Based on research by PT Mitra Antar Putra using the reach, meet and close strategy, through various strategies that have been compiled in the SWOT table, 3 alternative strategies were selected according to the form of creating new features that did not exist, evaluating the form of promo and the results to create a new promotion, overhauling the rules special or new for the Sales Team to acquire equally in each category. Based on the personal selling strategy, the alternative strategy "revises special or new rules for the Sales Team to acquire equally in each category.